The clinical and cost-effectiveness of rehabilitation of memory in brain injury: the ReMemBrIn RCT - das Nair, Roshan; Bradshaw, Lucy E.; Carpenter, Hannah; Clarke, Sara; Day, Florence; Drummond, Avril; Fitzsimmons, Deborah; Harris, Shaun; Montgomery, Alan A.; Newby, Gavin; Sackley, Catherine; Lincoln, Nadina B. (NIHR Health Technology Assessment Programme, 2017)
Background People with traumatic brain injuries (TBIs) commonly report memory impairments. These are persistent, debilitating, and reduce quality of life, but patients do not routinely receive memory rehabilitation after discharge from hospital. Objectives To assess the clinical and cost-effectiveness of a group memory rehabilitation programme for people with TBI.